SCIENTISM AND ROMAN CATHOLIC THEOLOGY: TOWARDS EXORCISING THE ZEITGEIST OF INSTITUTIONALIZED TRUTH?. Issue 42 (9th December 2015) - Dunne, Gerry
Abstract : In a fable by Lincoln Steffens, he recounts the fate of a man, who, climbing to the top of a mountain, seizes hold of the Truth. Satan, suspecting mischief from this upstart, duly directs his underlings to tail him. When the demon reports with alarm the man's success – that he had indeed seized hold of the Truth – Satan remains unperturbed. 'Don't worry', he yawned. 'I'll tempt him to institutionalize it.' 1 The purpose of this paper is to offer an exploratory critique of the concept of institutionalized truth, as it is postulated within the epistemic traditions of scientism and Roman Catholic theology. Drawing on examples from each of these paradigms, namely, the conclusions of scientism, and the doctrine of papal infallibility, this disquisition argues that immutable truths, as championed by both camps, are in fact, questionable constructs, open to interpretation and criticism.